A VLSI Implementation of Rank-Order Searching Circuit Employing a Time-Domain Technique - Trong-Tu Bui; Tadashi Shibata (Journal of Engineering)
We present a compact and low-power rank-order searching (ROS) circuit that can be used for building associative memories and rank-order filters (ROFs) by employing time-domain computation and floating-gate MOS techniques. The architecture inherits the accuracy and programmability of digital implementations as well as the compactness and low-power consumption of analog ones. We aim to implement identification function as the first priority objective. Filtering function would be implemented once the location identification function has been carried out. The prototype circuit was designed and fabricated in a 0.18 μm CMOS technology. It consumes only 132.3 μW for an eight-input demonstration case.